Sucralose Promotes Colitis-Associated Colorectal Cancer Risk in a Murine Model Along With Changes in Microbiota - Li, Xueting; Liu, Yuanli; Wang, Yan; Li, Xue; Liu, Xinran; Guo, Mengru; Tan, Yiwei; Qin, Xiaofa; Wang, Xiuhong; Jiang, Mingshan (Frontiers in Oncology, 2020)
Sucralose is a calorie-free high-intensity artificial sweetener that is widely used in thousands of foods and beverages all over the world. Although it was initially regarded as a safe, inert food additive, its adverse effect on gut microbiota and health has drawn more and more attention as evidence accumulates. Studies by us and others revealed that sucralose exacerbated gut damage and inflammation in animal models for inflammatory bowel disease (IBD), including those for both ulcerative colitis, and Crohn's disease. Our study demonstrated that sucralose greatly aggravated dextran sulfate sodium (DSS)-induced colitis along with causing changes in gut microbiota, the gut barrier and impaired inactivation of digestive proteases mediated by deconjugated bilirubin. It is well-documented that IBD greatly increases the risk of colorectal cancer (CRC), the globally third-most-common cancer, which, like IBD, has a high rate in the developed countries. Azoxymethane (AOM)/DSS has been the most commonly used animal model for CRC. In this study, we further explored the effect of sucralose on tumorigenesis and the possible mechanism involved using the AOM/DSS mouse model. First, 1.5 mg/ml sucralose was included in the drinking water for 6 weeks to reach a relatively stable phase of impact on gut microbiota. Then, 10 mg/kg AOM was administered through intraperitoneal injection. Seven days later, 2.5% DSS was put in the drinking water for 5 days, followed by 2 weeks without DSS. The 5 days of DSS was then repeated, and the mice were sacrificed 6 weeks after AOM injection. The results showed that sucralose caused significant increases in the number and size of AOM/DSS-induced colorectal tumors along with changes in other parameters such as body and spleen weight, pathological scores, mortality, fecal β-glucuronidase and digestive proteases, gut barrier molecules, gut microbiota, inflammatory cytokines and pathways (TNFα, IL-1β, IL-6, IL-10, and TLR4/Myd88/NF-κB signaling), and STAT3/VEGF tumor-associated signaling pathway molecules. These results suggest that sucralose may increase tumorigenesis along with dysbiosis of gut microbiota, impaired inactivation of digestive protease, damage to the gut barrier, and exacerbated inflammation.